KEEFEKTIFAN PENGGUNAAN MODEL COOPERATIVE LEARNING TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) DALAM KEMAMPUAN MEMBACA TEKS BAHASA JERMAN SISWA KELAS X MIPA SMA NEGERI 1 BARRU - Yuniar Hidayah Sanusi; Misnah Mannahali; Muhammad Anwar (Universitas Negeri Makassar, 2020)
Abstract. This research was conducted to obtain data and information about the effectiveness of the use of cooperative learning models of Student Teams Achievement Divisions (STAD) type in learning the ability to read German text in class X MIPA students of SMA Negeri 1 Barru. This type of research is a Quasi Experiment using Pretest-Posttest Control Group Design. The study population is all students of class X MIPA SMA 1 Barru consisting of 3 classes with a total of 98 people. The sample in this study were students of class X MIPA 4 with a total of 28 people as an experimental group and students of class X MIPA 5 with a total of 28 people as a control group. Research data were collected using a test of reading German text skills. Retrieval of data using pretest and posttest. The results of data analysis show that Z-count has a value of -3.664 which is smaller than Z-table which is 0.67. This means that H0 is rejected. The results of this analysis mean that the cooperative learning model type Student Teams Achievement Divisions (STAD) is effective in improving the ability to read German text in Class X MIPA Students in SMA Negeri 1 Barru.